Pengaruh Disiplin Kerja, Motivasi Dan Kompetensi Terhadap Kinerja Karyawan Pada PT. Pelindo IV Cabang Makassar - rostini rostini; Muh Hasry Mukhtiali; Nurfatwa Andriani Yasin; Jumiati Nurdin (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
This study aims to determine the effect of work discipline, motivation and competence on employee performance at PT. Pelindo IV Makassar Branch. The method used is multiple regression analysis using a questionnaire. The sample in this study were employees of PT. Pelindo IV (Persero) Makassar Branch which was selected through the Census method with a total of 50 employees. The results of this study indicate that based on the partial test, the Work Discipline variable (X1) has a positive and significant effect on the Performance variable (Y), the Motivation variable (X2) has a positive and significant effect on the Performance variable (Y), and the Competence variable (X3) also has a positive effect. and significant to the Performance variable (Y). While the results of the simultaneous test of Work Discipline variable (X1), Motivation variable (X2) and Competence variable (X3) simultaneously have a positive and significant effect on Employee Performance (Y). The variable that has a more dominant influence is the competence variable.